PENINGKATAN KESADARAN DAN KEMAMPUAN ANAK DALAM CUCI TANGAN PAKAI SABUN (CTPS) 20 DETIK PADA MASA LIBUR SEKOLAH DI MASA PANDEMI COVID 19 - Nasution, Nurul Hidayah (Universitas Aufa Royhan Di Kota Padangsidipuan, 2021)
The corona pandemic has now hit 216 countries. The total number of positive cases of Covid-19 worldwide until February 2021 was 109 million. Data on the development of Covid-19 in North Sumatra until February 2021, there were 22,865 positive corona patients with 781 cases of dead patients and 19,641 recovered patients. School is a very effective place in order to improve the health status of the community. The purpose of community service is to aim for elementary school students to increase awareness and ability to wash their hands with soap for 20 seconds during school holidays as protection to prevent the spread of COVID-19. Socialization is carried out using posters. The population and sample of this service are elementary school students with a total of 30 people. The results of this community service were enthusiastically received by elementary school students in class at SD Negeri No. 200308 Padangsidimpuan City as seen from the number of elementary school students who asked about information about covid-19, the spread of covid-19 and how to wash hands with soap for 20 seconds correctly in everyday life. It is recommended that socialization activities to increase awareness and ability to wash hands with soap for 20 seconds during school holidays can be carried out regularly with a more frequent frequency and the range of information dissemination can also be expanded to families of elementary school students in general so that everyone, families and communities better know, understand and be able to practice efforts to prevent the spread of covid-19 in daily life through the movement of washing hands with soap for 20 seconds so that ultimately it can improve the health status of the community.